Observation on Marine Copepod - Appendicularian Naturally Changing Concentrations Along Southwest Coast of India - Jean J. JOSE; Aaron P. LIPTON; Lincy ALEX; Purayath UDAYAKUMAR; Bhama R. RAJESH; Mary Teresa P. MIRANDA (Notulae Scientia Biologicae, 2012)
Patterns of copepod - appendicularian distribution were studied along the Mangalore coastal waters (125049 N; 744850 E) of the Arabian Sea to understand the food and feeding relationship existing among these groups. Sampling was conducted during pre-monsoon, monsoon and post-monsoon extending from January 2009 to December 2010. The copepod and appendicularian community was sampled with a 60 ?m net to include the smallest species and their developmental stages. Copepod biomass, especially calanoids, was substantially high throughout the study. Seasonal mean results showed that the small-sized copepods (calanoids, harpacticoida and cyclopoids) dominated in terms of biomass and production. Calanoids found in abundance included Acartia, Centropages, Calanus, Eucalanus and Labidocera. Cyclopoid and Harpacticoid copepods genera dominated included Oithona, Oncaea and Microsetella, Macrosetella. Appendicularian species diversity was represented by Oikopleura fusiformis, O. dioica and its juveniles represented as Oikopleura sp. Total chlorophyll (chlorophyll a) ranging between 10 and 20 mg m-3 indicated the eutrophic state as well as productivity prevailing during the study period. Principal component analysis (PCA) indicated the routine and opportunistic seasonal grazers and establishes a phytoplankton - appendicularia - copepod - fish food chain relationship along Mangalore coast.